PENERAPAN DISIPLIN POSITIF MELALUI KESEPAKATAN KELAS UNTUK MENINGKATKAN KEMANDIRIAN PESERTA DIDIK KELAS VIII-G MAPEL PENDIDIKAN PANCASILA DI SMPN 39 SURABAYA - Sakina Anindya Putri; Maya Mustika Sari; Binti Ismiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted based on the problem identified in class VIII-G, where the students' level of independence was found to be very low. The classroom action research aimed to improve students' independence through a classroom agreement designed to instill good habits among the students in class VIII-G. This approach encourages disciplined behavior towards the tasks assigned to them, as a form of responsibility they must fulfill as students. Additionally, it aligns with one of the dimensions of the Pancasila Student Profile, namely: possessing a spirit of independence. The data collection techniques used in this study included observation activities and assessment instruments in the form of observation sheets and questionnaires, using a qualitative approach. The research was conducted over two cycles, Cycle I and Cycle II. The results of the study showed an increase in each cycle. The aspects of independence improved steadily in each cycle after the implementation of positive discipline through classroom agreements. These findings suggest that positive discipline through classroom agreements can serve as a reference when similar issues are encountered in classroom teaching.